(untitled) (Journal of the College of Basic Education, 2022)
The percent of lead content in gasoline that obtained from one of the fuel stations in Baghdad was 52.5 mg/ L., locally isolate from yeast Saccharomyces boulardii was used to removed lead from gasoline after make sure it’s by morphological and biochemical tests.It was observed an increase in the efficiency of the removal of lead level by increased duration of contact between material adsorbent (yeast) and gasoline, the removal percent were 67 and 79% when the duration of contact were 15 and 30 minutes respectively, to up to 87% when the duration of contact was 60 minutes to stop after which the percentage removal at this level despite increasing the duration of contact to 90 and 120 minutes. The increase in weight of adsorbent lead to increase the removal of lead element percent until it reaches a certain point did not lead with the increase in weight to increase the proportion of the removal, as the percentage of removal of 45.8, 87 and 89, 95 and 97 and 97% when the weight of material adsorbent amount of 0.05 to 0.1 and 0.2 and 0.3, 0.4 and 0.5gm respectively. The highest removal efficiency of lead was 96% at 150 rpm/ min, while it was 73, 82 and 94% at 50, 100 and 125 rpm/ min respectively, while increasing the stirring speed to 175 and 200 r / min was not effect to increase the efficiency of the removal of lead that it remain at 96%.